Clinical and genetic features of eight Chinese autosomal-dominant optic atrophy pedigrees with six novel OPA1 pathogenic variants. (3rd September 2018) - Li, Huajin; Jones, Evan M.; Li, Hui; Yang, Lizhu; Sun, Zixi; Yuan, Zhisheng; Chen, Rui; Dong, Fangtian; Sui, Ruifang
ABSTRACT: Background: Autosomal-dominant optic atrophy (ADOA) is one of the most common types of inherited optic atrophy. We identify OPA1 pathogenic variants and assess the clinical features of a cohort of Chinese ADOA patients Materials and Methods : Detailed clinical evaluations were performed and genomic DNA was extracted from peripheral blood for all the participants. Sanger sequencing was used to analyze all exons and exon/intron junctions of OPA1 for eight pedigrees. Target exome capture plus next-generation sequencing (NGS) were applied for one atypical family with photophobia. Reverse transcription polymerase chain reaction was carried out to further characterize the mRNA change of selected splicing alteration. Results: All 17 patients had impaired vision and optic-disk pallor; however, the clinical severity varied markedly. Two patients complicated with hearing loss. Six novel and two reported pathogenic variants in OPA1 (GenBank Accession No. NM_130837.2) were identified including four nonsynonymous variants (c.2400T > G, c.1468T > C, c.1567A > G and c.1466T > C), two splicing variants (c.2984-1_2986delGAGA and c.2983 + 5G > A), one small deletion (c.2960_2968delGCGTTCAAC), and one small insertion (c.3009_3010insA). RNA analysis revealed the splicing variant c.2984-1_2986delGAGA caused small deletion of mRNA (r.2983_2988del). Conclusions: ADOA patients presented variable clinical manifestations. Novel OPA1 pathogenic variants are the main genetic defect for Chinese ADOA cases. NGS may be a useful molecular testing tool for atypical ADOA.